2018
DOI: 10.1016/j.catena.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

PEATMAP: Refining estimates of global peatland distribution based on a meta-analysis

Abstract: Peatlands play important ecological, economic and cultural roles in human well-being. Although considered sensitive to climate change and anthropogenic pressures, the spatial extent of peatlands is poorly constrained. We report the development of an improved global peatland map, PEATMAP, based on a meta-analysis of geospatial information collated from a variety of sources at global, regional and national levels. We estimate total global peatland area to be 4.23 million km 2 , approximately 2.84 % of the world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
453
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 575 publications
(473 citation statements)
references
References 45 publications
14
453
0
6
Order By: Relevance
“…The use of modern-day topography to calculate the extent of peatland during the Holocene might thus overestimate Holocene peatland expansion rates for some regions, exacerbating the positive feedback of peatland HSU on area in our model.The overestimation of the area of northern peatlands might cause biases on the simulated peatlands NEP. We estimate this impact crudely by masking the model result with an observation-based peatland map [meaning that only grid cells that have peatland in PEATMAP(Xu et al, 2018) are accounted for]; the simulated present-day northern peatlands area after masking is 4.4 (IPSL-CM5A-LR) and 4.6 million km 2 (GFDL-ESM2M), closer to previous estimates of 3.4-4 million km 2 . These peatlands are predicted to sequester 13 (IPSL-CM5A-LR under both RCP2.6 and RCP6.0) and 16 PgC (GFDL-ESM2M under both RCP2.6 and RCP6.0) over2006- 2099…”
mentioning
confidence: 62%
“…The use of modern-day topography to calculate the extent of peatland during the Holocene might thus overestimate Holocene peatland expansion rates for some regions, exacerbating the positive feedback of peatland HSU on area in our model.The overestimation of the area of northern peatlands might cause biases on the simulated peatlands NEP. We estimate this impact crudely by masking the model result with an observation-based peatland map [meaning that only grid cells that have peatland in PEATMAP(Xu et al, 2018) are accounted for]; the simulated present-day northern peatlands area after masking is 4.4 (IPSL-CM5A-LR) and 4.6 million km 2 (GFDL-ESM2M), closer to previous estimates of 3.4-4 million km 2 . These peatlands are predicted to sequester 13 (IPSL-CM5A-LR under both RCP2.6 and RCP6.0) and 16 PgC (GFDL-ESM2M under both RCP2.6 and RCP6.0) over2006- 2099…”
mentioning
confidence: 62%
“…This study confirmed that the natural wetlands act as GHG sinks or are neutral. Considering the global area of coastal wetlands (1.28 × 10 5 km 2 ; Murray et al, 2019), riparian wetlands (3.69 × 10 6 km 2 ; Lehner & Döll, 2004), and peatlands (4.23 × 10 6 km 2 ; Xu, Morris, Liu, & Holden, 2018), the annual GHG uptake by the three types of natural wetlands would be around 0.01, 3.23, and 1.21 Gt CO 2 -eq/year, respectively, which are comparable to the results of Lu et al (2017). However, both analytical methods of data (with total 209 sites or 178 strictly controlled sites)…”
Section: Ghg Budget Of Lulcc From Natural Wetlandsmentioning
confidence: 99%
“…In addition to moisture availability, a lower water table alters nutrient availability by decreasing the flow of groundwater to fens, which in turn changes the competitive balance of many wetland species (Granath, Strengbom, & Rydin, 2010;Laine et al, 1995;Nijp et al, 2014). Significant changes are to be expected in boreal regions, which foster the majority of peatlands globally, as they are some of the fastest warming places on earth (IPCC, 2014;Solomon, Qin, Manning, Averyt, & Marquis, 2007;Xu, Morris, Liu, & Holden, 2018).…”
Section: Introductionmentioning
confidence: 99%